2014
DOI: 10.1051/0004-6361/201323091
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale magnetic fields in Bok globules

Abstract: Context. The role of magnetic fields in the star formation process is a contentious matter of debate. In particular, no clear observational proof exists of a general influence by magnetic fields during the initial collapse of molecular clouds. Aims. Our aim is to examine magnetic fields and their influence on a wide range of spatial scales in low-mass star-forming regions. Methods. We trace the large-scale magnetic field structure on scales of 10 3 −10 5 AU in the local environment of Bok globules through opti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
49
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 46 publications
9
49
2
Order By: Relevance
“…In the case of globules B335, CB230 and CB68, the outflows are oriented almost perpendicular to the inner magnetic field (Wolf et al 2003;Bertrang et al 2014). Bertrang et al (2014) also reported that the magnetic field orientation of CB54 is aligned with CO outflow.…”
Section: Correlation Between Magnetic Field and Outflowsmentioning
confidence: 85%
See 3 more Smart Citations
“…In the case of globules B335, CB230 and CB68, the outflows are oriented almost perpendicular to the inner magnetic field (Wolf et al 2003;Bertrang et al 2014). Bertrang et al (2014) also reported that the magnetic field orientation of CB54 is aligned with CO outflow.…”
Section: Correlation Between Magnetic Field and Outflowsmentioning
confidence: 85%
“…They commented that in those sources the fields have been wrapped up toroidally by envelope rotation. Many observations have been reported to study the correlation between magnetic field and CO outflow of the Bok globules (e.g., Cohen et al (1984); Vrba et al (1986); Jones & Amini (2003); Wolf et al (2003); Hull et al (2013);Bertrang et al (2014); Soam et al (2015)). Some study shows a good alignment of globule's magnetic field with outflow axis (e.g., Cohen et al (1984); Vrba et al (1986); Jones & Amini (2003)), whereas misalignment of magnetic field direction and outflow axis have been also reported (e.g.…”
Section: Correlation Between Magnetic Field and Outflowsmentioning
confidence: 99%
See 2 more Smart Citations
“…The polarization measurements in optical (e.g., Vrba et al 1976;Goodman et al 1990;Alves et al 2008;Soam et al 2013;Alves et al 2014), near-infrared (e.g., Goodman et al 1995;Chapman et al 2011;Sugitani et al 2011;Clemens 2012;Cashman & Clemens 2014;Bertrang et al 2014;Kusune et al 2015;Alves et al 2014) and submillimeter-millimeter wavelengths (e.g., Rao et al 1998;Dotson et al 2000Dotson et al , 2010Vaillancourt & Matthews 2012;Hull et al 2014;Alves et al 2014) are used to map the magnetic field geometry of molecular clouds. Optical polarization position angles trace the plane of the sky orientation of the ambient magnetic field at the periphery of the molecular clouds (with A V ∼ 1-2 mag; Goodman et al 1995;Goodman 1996).…”
Section: Introductionmentioning
confidence: 99%